Molecular Characterization of Culturable Yeasts and Nonspore-Forming Bacteria Associated With Fermented Kapok Seeds (Kantong), a Traditional Food Condiment in Ghana - Elmer Nayra Ametefe; Line Thorsen; Harry Danwonno; Righteous Kwaku Agoha; Richard L. K. Glover; Victoria Pearl Dzogbefia; Lene Jespersen (International Journal of Food Science)
Fermented kapok seeds, known as kantong in northern Ghana, serve as a traditional food condiment which provides flavor and improves the protein content of soups. In this study, the occurrence of yeasts, lactic acid bacteria (LAB), and other nonspore-forming bacteria in kantong was investigated. Microbial enumeration and phenotypic characterizations on isolated strains were performed. Molecular methods were also employed for grouping and identification of strains, and these included random amplification of polymorphic DNA (RAPD) using Escherichia coli phage–derived M13 primer (M13-PCR typing), repetitive element PCR typing (rep-PCR), and 16S rRNA gene sequencing. After a 48-h fermentation period, microbial load ranged from 4.77±0.11 to 8.9±0.1 log10 CFU/g. The pH of the fermenting condiment decreased from 6.5 to 4.7 during the fermentation period. A total of 190 LAB, 53 enterobacteria, and 39 yeasts were identified at species levels using both phenotypic and molecular methods. The LAB included Pediococcus acidilactici, Weissella paramesenteroides, Pediococcus pentosaceus, Weissella confusa, and Lactiplantibacillus plantarum; the enterobacteria isolated were Acinetobacter baumannii, Klebsiella pneumoniae, Enterococcus faecium, Escherichia coli, and Enterobacter cloacae; and the yeasts identified were Nakaseomyces glabratus, Cyberlindnera fabianii, Pichia kudriavzevii, and Saccharomyces cerevisiae. This work presents fermented kapok seeds as a reservoir of microorganisms, some of which could possess some technological properties which could be harnessed to enhance the nutritional value of Ghanaian foods as well as improve gut health as probiotics. It also reveals the presence of enterobacteria in this spontaneous fermentation, thus impacting the safety of the product and the need for starter culture development.